Decomposition of corn and soybean residues under field conditions and their role as inoculum source - Reis,E.M. (2011)
Necrotrophic parasites of above-ground plant parts survive saprophytically, between growing seasons in host crop residues. In an experiment conducted under field conditions, the time required in months for corn and soybean residues to be completely decomposed was quantified. Residues were laid on the soil surface to simulate no-till farming. Crop debris of the two plant species collected on the harvesting day cut into pieces of 5.0cm-long and a 200g mass was added to nylon mesh bags. At monthly intervals, bags were taken to the laboratory for weighing. Corn residues were decomposed within 37.0 months and those of soybean, within 34.5 months. Hw main necrotrophic fungi diagnosed in the corn residues were Colletotrichum gramicola, Diplodia spp. and Gibberella zeae, and those in soybeans residues were Cercospora kikuchii, Colletotrichum spp, Glomerella sp. and Phomopsis spp. Thus, those periods shoulb be observed in crop rotation aimed at to eliminating contaminated residues and, consequently, the inoculum from the cultivated area.